Optimalisasi Metode Pembelajaran Berbasis Kebutuhan Peserta Didik Untuk Meningkatkan Keterlibatan Dan Prestasi Di SDN 1 Trusmi Kulon - Nurkholis; Ayesha Ziaurrakhman; Lelly Winoja Harum Sari; Amrina Rosada (PT. Hasba Edukasi Mandiri, 2025)
This study aims to understand and optimize student-centered learning methods at SDN 1 Trusmi Kulon to improve engagement and learning achievement. It focuses on the problem of misalignment between teaching methods and the unique needs of students, impacting motivation and academic outcomes. A qualitative method with a case study approach is used to deeply analyze adaptive teaching strategies. Data is collected through participant observation, in-depth interviews with teachers and students, and analysis of learning documents. The results show that active learning methods and student-centered approaches, implemented with sensitivity to context and individual needs, contribute significantly to improved student engagement, understanding, and achievement. Teacher training is also identified as an important factor in supporting successful implementation. In conclusion, a deep understanding of student needs and classroom context, along with the implementation of adaptive and responsive teaching methods, can create an inclusive learning environment. Recommendations are given to continue developing teaching strategies that are personal and relevant to student needs